Plasma mineral profile in relation to pregnancy rate in repeat breeding cows - PRASAD, J K; SINGH, BERENDRA; GUPTA, H P; KUMAR, MAHESH (The Indian Journal of Animal Reproduction, 2007)
Thirty eight crossbred cows were taken with the history of repeat breeding condition to study the plasmamineral profile viz. copper (Cu), cobalt (Co), zinc (Zn), magnesium (Mg) and calcium (Ca) in relation topregnancy rate. The percentage of aninlals significantly deficient in plasma level of Cu, Co, Zn, Mg and Ca were34.21%, 21.05%, 44.74%, 42.10% and 26.32%, respectively. All the animals were inseminated in the subsequentestrus and pregnancy rate was confirmed by palpation per-rectum. The pregnancy was significantly lower in theanimals deficient in Cu (64.00% in normal cows' vs 7.70% in deficient cows) and Zn (57.00% in normal cows' vs23.53% in deficient. cows). The present study clearly indicates that minerals viz. Cu, Co, Zn, Mg and Ca areessential for optimum fertility; however, deficiency of Cu and Zn plays a significant role in reducing theconception rate.
Keywords: Crossbred cow; Plasma mineral; Pregnancy rate